SPESIES - SPESIES JAMUR ENTOMOPATOGEN YANG MENGINFEKSI Aphis gossypii (GLOVER) (HEMOPTERA: APHIDIDAE) DI AGROEKOSISTEM SAYUR DATARAN RENDAH DAN DATARAN TINGGI SUMATERA SELATAN - Siti Herlinda, Riyanto (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
This research was aimed at exploring and identifying the entomopathogen fungi Aphis gossypii (Glover) (Hemoptera: Aphidiidae) in the agroecosystem of the lowland and highland of South Sumatra. The surveys of the entomopathogen A. gossypii were conducted in 11 locations of the vegetable centers of South Sumatra.  The Identification of entomopathogen was conducted in the Laboratory of the Entomology, Department of Pests and Plant Diseases, Faculty of Agriculture, Sriwijaya University.  This research was conducted during the period of July 2009 and July 2010. The results of the study also revealed that two species of entomopathogenic fungi: M. anisopliae and B. bassiana were found. In the medium culture, B. bassiana colony was white and formed a bundle like cotton.  When it reached the age of over 10 days old, it looked like yellowish white chalk.  The spores of  B. bassiana were oval, with an average length of 3 μm, white in color and grow  in zigzag form from conidiospores.  In the medium culture , M. anisopliae colony was greenish yellow in color and forms spots.  The spores of  M. anisopliae were green in color, cylindrical in form with an average length of 10 μm and form a chain. Key words: Aphis gossypii (Glover), Beauveria bassiana (Balsamo) and Metarrhizium anisopliae (Metsch)